Real-world cost-effectiveness of drug-eluting stents vs. bare-metal stents for coronary heart disease—A five-year follow-up study. Issue 2 (February 2019) - Cheng, Hao-Min; Chiou, Ling-Jan; Chen, Tzu-Ching; Sung, Shih-Hsien; Chen, Chen-Huan; Lang, Hui-Chu
Highlights: DES was related to better outcomes than for BMS. The long term cost-effectiveness of DES vs. BMS is not clear. The NHI should reimburse the DES instead of current balance billing. Abstract: Objective: To evaluate the cost-effectiveness of using drugeluting stents (DES) compared to bare-metal stents (BMS) for coronary heart disease (CHD). Data sources/study setting: Data were obtained from the National Health Insurance Longitudinal Health Insurance Database, which contains claims data for 1, 000, 000 beneficiaries. The data were randomly sampled from all beneficiaries. Study design: A retrospective claims data analysis. Data collection/extraction methods: Patients with stable coronary heart disease who underwent coronary stent implantation from 2007 to 2008 were recruited and followed to the end of 2013. After a 2:1 propensity score matched by gender, age, stent number, and the Charlson comorbidity index (CCI), 852 patients with 568 stents in the BMS group and 284 stents in the DES group were included. The cumulative medical costs for both matched groups were estimated with the Kaplan-Meier Sample Average (KMSA), and then the incremental cost-effectiveness ratio (ICER) was estimated. Principal findings: The ICER of DES vs. BMS was NT 663, 000 per cardiovascular death averted and NT 238, 394 per cardiovascular death or coronary event averted in five years from the insurer perspective. Conclusion: Percutaneous coronary intervention (PCI) with DES was a more cost-effective strategy than PCI with BMS for CHD patients during the five-year follow-up.